The effect of tetrabromobisphenol A on protamine content and DNA integrity in mouse spermatozoa - Zatecka, E; Castillo, J; Elzeinova, F; Kubatova, A; Ded, L; Peknicova, J; Oliva, R (Andrology, 2014)
Tetrabromobisphenol A (TBBPA) is a widely used brominated flame retardant of increasing concern to human health because of its action as an endocrine disruptor. We have previously demonstrated that TBBPA is able to increase apoptosis of testicular cells and other changes in the first and second generations of mice exposed to TBBPA. However, the potential effects of TBBPA on mouse epididymal spermatozoa have not yet been investigated. Therefore, we initiated this study to determine whether TBBPA exposure could also result in increased DNA fragmentation in epididymal spermatozoa and whether it had an effect on the protamines as the major nuclear proteins. C57Bl/6J mouse pups (n = 10) were exposed to TBBPA (experimental group) during the gestation, lactation, pre-pubertal and pubertal periods up to the age of 70 days as previously described and compared to control mouse pups (n = 10) that were not exposed. The results demonstrate that TBBPA treatment results in a significantly decreased protamine 1/protamine 2 ratio (0.362 vs. 0.494; p < 0.001), increased total protamine/DNA ratio (0.517 vs. 0.324; p < 0.001) and increased number of terminal deoxynucleotidyl transferase dUTP nick end labelling positive spermatozoa (39.5% vs. 21.2%; p < 0.05) observed between TBBPA and control mice respectively. These findings indicate that TBBPA exposure, in addition to the resulting increased sperm DNA damage, also has the potential to alter the epigenetic marking of sperm chromatin through generation of an anomalous content and distribution of protamines. The possibility is now open to study whether the detected altered protamine content and DNA integrity are related to the previously observed second-generation effects upon TBBPA exposure.
Keywords: spermie; sekvence nukleotidů; DNA primery; trijodthyronin; Polybrominated Biphenyls; Triiodothyronine; polymerázová řetězová reakce s reverzní transkripcí; Reverse Transcriptase Polymerase Chain Reaction; zvířata; myši; polybrombifenylové sloučeniny; myši inbrední C57BL; Mice; DNA; Base Sequence; Male; Testosterone; protaminy; Mice, Inbred C57BL; DNA Primers; Protamines; poškození DNA; DNA Damage; Spermatozoa; Animals; mužské pohlaví; testosteron